Integrating reading and writing to facilitate reading engagement through epistolary writing among ESL tertiary students / Puteri Rohani Megat Abdul Rahim - Megat Abdul Rahim, Puteri Rohani (Universiti Teknologi MARA, Kedah, 2015)
This study examines the pedagogical perspective of employing epistolary writing in a reading program. Reading and writing have traditionally been taught separately. However, researchers have increasingly noted the connections between reading and writing as having similar processes of meaning construction. Writing when integrated with reading permits meaningful engagement between reader and text. In this qualitative case study, epistolary writing or letter writing is employed to capture the students’ understanding and reflection of their reading as well as on what has been taught by the instructor in the classroom. Three students took part in the study. Data were obtained through observations, interviews, and students’ written documents. The findings reveal conditions that enhance and hamper engagement among the students. The students reported the process of writing enabled them to strengthen their understanding of the texts assigned to them. In addition, aspects of pedagogy found useful by students were also identified. However, lecturers need to expose students the purpose of writing before employing it in the reading class. Discussion will focus on implications from insights gained and instructional practice in second language education.